Rezolvati in multimea numerelor intregi urmatoarele ecuatii:
a) 2x + 1 =-7
b)3x-1=-13
c)2x+15 =5
d)2x+10=0
e)3x+24=0
f)-2x+1=-7
g)-3x+1=-14
h)-5x+1=1
i)3+2x=-7
j)5+2x =-11
k)6+3x=-54
l) 1+9x=-89
m)1-2x=-7
n)5-4x=-3
o) 1-6x=-11
p)1-5x=-19
Răspunsuri la întrebare
Răspuns:
Explicație pas cu pas:
a)
2 x + 1 = - 7
2 x = - 7 - 1
2 x = - 8
x = ( - 8 ) : 2
x = - 4
Verific:
2 x + 1 = 2 × ( - 4 ) + 1 = - 8 + 1 = - 7
___________________________
b)
3 x - 1 = - 13
3 x = - 13 + 1
3 x = - 12
x = ( - 12) : 3
x = - 4 ∈ Z
Verific:
3 x - 1 = 3 × ( - 4 ) - 1 = - 12 - 1 = - 13
___________________________
c)
2 x + 15 = 5
2 x = 5 - 15
2 x = - 10
x = ( - 10) : 2
x = - 5
Verific:
2 x + 15 = 2 × ( - 5 ) + 15 = - 10 + 15 = 5
_____________________________
d)
2 x + 10 = 0
2 x = 0 - 10
2 x = - 10
x = ( - 10 ) : 2
x = - 5 ∈ Z
Verific:
2 x + 10 = 2 × ( - 5 ) + 10 = - 10 + 10 = 0
_____________________________
e)
3 x + 24 = 0
3 x = - 24
x = ( - 24 ) : 3
x = - 8
Verific: 3 x + 24 = 3 × ( - 8 ) + 24 = - 24 + 24 = 0
____________________________________
f)
- 2 x + 1 = - 7
- 2 x = - 7 - 1
- 2 x = - 8
x = ( - 8 ) : ( - 2 )
x = 4
Verific: - 2 x + 1 = ( - 2 ) × 4 + 1 = - 8 + 1 = - 7
_________________________________
g)
- 3 x + 1 = - 14
- 3 x = - 14 - 1
- 3 x = - 15
x = ( - 15 ) : ( - 3 )
x = 5 ∈ Z
Verific: - 3 x + 1 = - 3 × 5 + 1 = - 15 + 1 = - 14
_________________________________
h)
- 5 x + 1 = 1
- 5 x = 1 - 1
- 5 x = 0 ⇒ x = 0 : ( - 5) ⇒ x = 0
Verific: - 5 x + 1 = - 5 × 0 + 1 = 0 + 1 = 1
_____________________________
i)
3 + 2 x = - 7
2 x = - 7 - 3
2 x = - 10
x = ( - 10 ) : 2
x = - 5
Verific: 3 + 2 x = 3 + 2 × ( - 5 ) = 3 - 10 = - 7
__________________________________
j)
5 + 2 x = - 11
2 x = - 11 - 5
2 x = - 16
x = ( - 16 ) : 2
x = - 8 ∈ Z
Verific: 5 + 2 x = 5 + 2 × ( - 8 ) = 5 - 16 = - 11
_________________________________
k)
6 + 3 x = - 54
3 x = - 54 - 6
3 x = - 60
x = ( - 60 ) : 3
x = - 20
Verific: 6 + 3 x = 6 + 3 × ( - 20 ) = 6 - 60 = - 54
____________________________________
l)
1 + 9 x = - 89
9 x = - 89 - 1
9 x = - 90
x = ( - 90 ) : 9
x = - 10
Verific: 1 + 9 x = 1 + 9 × ( - 10 ) = 1 - 90 = - 89
____________________________________
m)
1 - 2 x = - 7
- 2 x = - 7 - 1
- 2 x = - 8
x = ( - 8 ) : ( - 2 )
x = 4
Verific: 1 - 2 x = 1 - 2 × 4 = 1 - 8 = - 7
________________________________
n)
5 - 4 x = - 3
- 4 x = - 3 - 5
- 4 x = - 8
x = ( - 8 ) : ( - 4 )
x = 2 ∈ Z
Verific: 5 - 4 x = 5 - 4 × 2 = 5 - 8 = - 3
______________________________
o)
1 - 6 x = - 11
- 6 x = - 11 - 1
- 6 x = - 12
x = ( - 12) : ( 6)
x = 2 ∈ Z
Verific: 1 - 6 x = 1 - 6 × 2 = 1 - 12 = - 11
____________________________
p)
1 - 5 x = - 19
- 5 x = - 19 - 1
- 5 x = - 20
x = ( - 20 ) : ( - 5)
x = 4 ∈ Z
Verific: 1 - 5 x = 1 - 5 × 4 = 1 - 20 = - 19